2017
DOI: 10.18632/oncotarget.17946
|View full text |Cite|
|
Sign up to set email alerts
|

The optimal time of initiation of renal replacement therapy in acute kidney injury: A meta-analysis

Abstract: BackgroundThe impact on the timing of renal replacement therapy (RRT) initiation on clinical outcomes for patients with acute kidney injury (AKI) remains controversial.Materials and methodsWe searched the Cochrane Library, EMBASE, Global Health, MEDLINE, PubMed, the International Clinical Trials Registry Platform, and Web of Science.ResultsWe included 49 studies involving 9698 patients. Pooled analysis of 5408 critically ill patients with AKI showed that early RRT was significantly associated with reduced mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Despite previous studies investigating the relationship between mortality and the timing of RRT initiation, it remained controversial whether early initiation of RRT improved outcomes. In 2016, two RCTs and in 2017 nine systematic reviews and meta‐analyses evaluated the optimal timing of RRT initiation for AKI. A multicenter RCT study, the Artificial Kidney Initiation in Kidney Injury (AKIKI) study, conducted in France, showed that there were no significant differences in mortality between early and late initiation of RRT .…”
Section: Rrt For Akimentioning
confidence: 99%
See 1 more Smart Citation
“…Despite previous studies investigating the relationship between mortality and the timing of RRT initiation, it remained controversial whether early initiation of RRT improved outcomes. In 2016, two RCTs and in 2017 nine systematic reviews and meta‐analyses evaluated the optimal timing of RRT initiation for AKI. A multicenter RCT study, the Artificial Kidney Initiation in Kidney Injury (AKIKI) study, conducted in France, showed that there were no significant differences in mortality between early and late initiation of RRT .…”
Section: Rrt For Akimentioning
confidence: 99%
“…Early initiation of RRT (defined as KDIGO stage 3 AKI) in the AKIKI study corresponded to the delayed arm in the ELAIN study. Turning to the conclusions of nine meta-analyses,[90][91][92][93][94][95][96][97][98] the AKI patients in the RCTs who underwent early initiation of RRT did not show a lower mortality rate than those with late RRT [90][91][92][93][94]96,98.…”
mentioning
confidence: 99%